Livestock Challenge Models of Rift Valley Fever for Agricultural Vaccine Testing - Kroeker, Andrea Louise; Babiuk, Shawn; Pickering, Bradley S.; Richt, Juergen A.; Wilson, William C. (Frontiers in Veterinary Science, 2020)
Since the discovery of Rift Valley Fever virus (RVFV) in Kenya, the virus has become widespread throughout most of Africa and is characterized by sporadic outbreaks. A mosquito-borne pathogen, RVFV is poised to move beyond the African continent into the Middle East and emerge in Europe and Asia. There is a risk that RVFV could also emerge in the Americas similar to the West Nile virus. In light of this potential threat, multiple studies have been undertaken to establish international surveillance programs and diagnostic tools, develop models of transmission dynamics and risk factors for infection, and to develop a variety of vaccines as countermeasures. Further, considerable efforts to establish reliable challenge models of Rift Valley Fever virus have been made to establish platforms for testing potential vaccines and therapeutics in target species. This review highlights the progress and insights from work performed to establish challenge models in livestock such as cattle, sheep, and goats to potential sentinel animals in white-tailed deer.